2012
DOI: 10.1155/2012/649753
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Low Fuel Regression Rate in Hybrid Rocket Engines

Abstract: Hybrid rocket engines are promising propulsion systems which present appealing features such as safety, low cost, and environmental friendliness. On the other hand, certain issues hamper the development hoped for. The present paper discusses approaches addressing improvements to one of the most important among these issues: low fuel regression rate. To highlight the consequence of such an issue and to better understand the concepts proposed, fundamentals are summarized. Two approaches are presented (multiport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 56 publications
0
30
0
7
Order By: Relevance
“…However, classical solid fuel hybrids have a diffusion-limited combustion process that takes places at the turbulent boundary layer and hence, their regression rate is still limited. Consequently, the improvement of their performance has been historically faced through three different approaches 3 : mitigation methods such as multiport grains, use of solid fuel additives and advanced oxidizer injector designs. Although multiport grains increase the fuel surface area for a given rocket size, they have many drawbacks (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, classical solid fuel hybrids have a diffusion-limited combustion process that takes places at the turbulent boundary layer and hence, their regression rate is still limited. Consequently, the improvement of their performance has been historically faced through three different approaches 3 : mitigation methods such as multiport grains, use of solid fuel additives and advanced oxidizer injector designs. Although multiport grains increase the fuel surface area for a given rocket size, they have many drawbacks (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The key operating principle is to alter the classical flow field in the combustion chamber in order to improve the heat transfer to the solid fuel grain surface and thus the regression rate. The most promising approaches are [18,60]: The solutions presented are mostly still investigated at a laboratory scale and need further researches, to better understand the scaling effects. This thesis is focussed on the last presented method, and especially on the swirl injection in sideburning grains, used to obtain a substantial increase of the combustion efficiency and of the regression rate.…”
Section: Chaptermentioning
confidence: 99%
“…In previous studies the authors analyzed the effect of the presence of uncertainties in the design parameters, such as in the regression rate, on rocket performance and mission goals [6,7]. Results showed that even small uncertainty in the determination of the regression rate may jeopardize vehicle performance and threaten seriously the mission.…”
Section: Introductionmentioning
confidence: 99%